Textual Plurality and Textual Reconstructions: A Cautionary Tale - Martone, Corrado (Revue de Qumran, 2018)
The Qumran texts show a great plurality of textual traditions and an even greater fluidity in the mode of transmission of these traditions. This holds true for both the texts which will be later part of a canon (the so-called 'biblical' texts) and for those that will not have the same fate (the so-called 'para-' and 'non-biblical' texts). This situation makes the task of reconstructing fragmentary, oftentimes very fragmentary texts difficult and risky. The present paper will present a number of examples aiming to show the possible pitfalls of reconstructions of texts stemming from a not uniform tradition, because variants may always be ''hiding themselves' in the lacunae' (F.M. Cross).